Creating space for leadership education in undergraduate medical education in Canada - Chan, Ming-Ka; Volk, Auriele; Patro, Nivedh; Lee, Wonjae; Sonnenberg, Lyn K; Dath, Deepak; de Camps Meschino, Diane (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
The need for effective leadership by physicians is clear, yet the design/delivery of curricula, and assessment of leadership competencies, in Undergraduate Medical Education (UGME) continues to need work. In reappraising their UGME assessment strategies, the Medical Council of Canada (MCC) invited position papers across diverse lenses, including the CanMEDS Intrinsic Roles. This article is foundational work derived from the report on leadership assessment to the MCC. Using Kern’s Model of Curriculum development as a guide, we reviewed the landscape of Canadian UGME leadership education through an environmental scan of the published and grey literature, Canadian leadership frameworks and resources, and consultation with learner and faculty leadership. Leadership education across programs was highly variable and learners were often unaware of available opportunities. In response, we have suggested processes for curricular development, including strategies for key content, teaching and assessment, and program evaluation considerations. Leadership education cannot remain another checkbox on a list of UGME experiences. Such training necessitates focused attention and investment to foster ongoing identity formation toward becoming a good doctor.